The Activity Evaluation Model and Sustainable Interactive Management Strategies of Online User Innovation Community - Wang, Zhigang; Wang (Avery. W), Yu; Wu, Shaobao (Sustainability, 2018)
With the development of social network, online user innovation communities (OUICs) become an important source where many companies gather valuable information for innovation development of their products or services. Activity is an important measure of whether an OUIC is developing normally. Therefore, it is crucial to understand what factors affect the activity of an OUIC, and how to increase it, so as to gain more insights from customers. So far, there has been scarce studies that examined activity in OUICs. To this end, first, we propose an evaluation model to assess activity of OUICs, and then we take two smartphone online communities as an example, namely Xiaomi community and Samsung community, to calculate and compare their activities. The result shows that the activity in Xiaomi community is higher than Samsung community during a certain period of time. Second, it is suggested that companies can improve activity of OUICs through increasing interaction in communities. We make an attempt to explore the factors that impact interaction in OUICs by conducting a questionnaire survey to OUIC users. It is found that environmental factors, information factors, personal factors, and trust factors mostly have a significant effect on interaction of OUICs. Finally, we put forward specific management strategies for improving the interaction of OUICs, according to our research findings.